Albumin-binding tag derived Exendin-4 analogue for treating hyperglycemia and diabetic complications - Shujuan Xu (Taylor & Francis Group, 2021)
Current study was conducted to design and screen a long-lasting Exendin-4 analog for treating type 2 diabetes via the novel strategy of albumin binding combined with thrombin enzymolysis. Firstly, a series of fusion peptides, containing different albumin-binding tags, a determinate thrombin-cleavable linker and a native Exendin-4, were prepared via chemosynthesis for in vitro and in vivo characterization. Surface plasmon resonance (SPR) assay, thrombin cleavage assay and plasma stability test were performed for screening the optimal HEX peptide with enhanced albumin-binding affinity, controlled-release as well as plasma stability. The in vivo anti-diabetic efficacies of the selected candidate were further assessed via both acute and chronic pharmacodynamic evaluation in diabetic model animals. HEX15 exhibited either the highest affinity for human serum albumin or the superior in vitro stability and controlled release of Exendin-4 among twenty-one HEX peptides. Glucose tolerance test and hypoglycemic duration assay both revealed the notably improved the glucose tolerance and prolonged normoglycemic duration, respectively, of diabetic mice after single treatment of HEX15. Furthermore, chronic dosing of HEX15 significantly ameliorated the manifestations of diabetes in the db/db mice, including body weight, food intake, glycometabolism as well as hyperlipaemia. Interestingly, combination therapy of HEX15 and long non-coding RNA-ENST00000411554 notably accelerated the wound healing and improved foot ulcer symptoms in model rats with diabetic foot ulcers. In summary, based on the strategy of linking the heptapeptide tag and thrombin-based sustained release, a long-acting Exendin-4 analogue, HEX15, holds potential to be developed as a drug for ameliorating T2D as well as diabetic complications.